Current status of cystic echinococcosis control in the Falkland Islands: has elimination been achieved?. Issue 5 (10th February 2023) - West, D.; Pointing, S.; Randhawa, H. S.; Mastin, A.; Rogan, M. T.
Abstract: Abstract: Attempts to control cystic echinococcosis (CE) caused by Echinococcus granulosus in the Falkland Islands have been ongoing for over 50 years. No human cases have been recorded since the 1980s but there is a need to establish if the parasite has been completely eliminated from domestic animals. A study was carried out in 2018/2019 to identify dogs infected with E. granulosus using copro-antigen and copro-polymerase chain reaction (PCR) analysis. In addition, annual slaughter data were analysed to establish infection levels of E. granulosus and 2 other taeniid parasites. Results showed that 4 out of 589 dogs (0.7%) tested positive by copro-antigen analysis. Results from similar surveys carried out in 2010, 2012 and 2014 showed 17 (3%), 0 and 6 (1%) copro-antigen-positive dogs, respectively, with 8 dogs being confirmed by PCR in 2010. Annual abattoir data showed that from 2006 to 2020, 36 sheep were identified with E. granulosus (mean 0.0055%), 14 186 sheep with Taenia hydatigena (mean 2.2%) and 465 with Taenia ovis (mean 0.072%). Prevalences of T. hydatigena and T. ovis showed spontaneous rises in certain years where the infections could also be detected in lambs indicating that viable taeniid eggs were present. Observations of farm management procedures indicated that there were occasions when dogs could get access to infective taeniid material. In conclusion, E. granulosus is still present in sheep and dogs but at low prevalences. The increasing presence of T. hydatigena however, indicates that control measures are defective in some areas and there is potential for a re-emergence of CE.